2020
DOI: 10.1002/humu.24067
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genotypic and phenotypic spectrum of severe serine biosynthesis disorders

Abstract: Serine biosynthesis disorders comprise a spectrum of very rare autosomal recessive inborn errors of metabolism with wide phenotypic variability. Neu–Laxova syndrome represents the most severe expression and is characterized by multiple congenital anomalies and pre‐ or perinatal lethality. Here, we present the mutation spectrum and a detailed phenotypic analysis in 15 unrelated families with severe types of serine biosynthesis disorders. We identified likely disease‐causing variants in the PHGDH and PSAT1 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…In addition to the two patients in this study, PSAT1 -related serine deficiency disorder have been reported in other 29 individuals including 13 males, 15 females, and one unidentified gender died in utero ( Table 2 ) ( Hart, et al, 2007 ; Acuna-Hidalgo, et al, 2014 ; Brassier et al, 2016 ; El-Hattab, et al, 2016 ; Glinton et al, 2018 ; Ni et al, 2019 ; Abdelfattah et al, 2020 ; Debs, et al, 2021 ). Fourteen patients came from consanguineous families.…”
Section: Resultsmentioning
confidence: 55%
“…In addition to the two patients in this study, PSAT1 -related serine deficiency disorder have been reported in other 29 individuals including 13 males, 15 females, and one unidentified gender died in utero ( Table 2 ) ( Hart, et al, 2007 ; Acuna-Hidalgo, et al, 2014 ; Brassier et al, 2016 ; El-Hattab, et al, 2016 ; Glinton et al, 2018 ; Ni et al, 2019 ; Abdelfattah et al, 2020 ; Debs, et al, 2021 ). Fourteen patients came from consanguineous families.…”
Section: Resultsmentioning
confidence: 55%
“…The plasma and CSF serine levels of the proband were comparable to those found in severely affected infants ( Table 2 ). Moreover, studies have indicated that phenotypic variability in serine deficiency disorders is mainly linked to the degree of PHGDH enzyme activity [ 16 , 38 ]. Here, we reported childhood phenotypes of PHGDH deficiency with microcephaly, intractable seizure, and developmental regression without hypomyelination.…”
Section: Discussionmentioning
confidence: 99%
“…PHGDH deficiency (MIM# 601815) is a rare, autosomal recessive disorder, characterized biochemically by low concentration of serine in the plasma and cerebrospinal fluid (CSF) and clinically by serious neurological problems [ 12 , 13 , 14 ]. The clinical phenotype varies from nonspecific neurodevelopmental delays to Neu–Laxova syndrome (NLS), an extremely lethal disease [ 15 , 16 ]. NLS has been identified in over 100 cases so far [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of the importance of PSP in the brain, it is not surprising that inborn deficiencies of PSP, as well as of the other enzymes in the phosphorylated pathway, are associated with neurological symptoms [11][12][13][14][15][16]. In mice, the knockout of both copies of associated with neurological symptoms [11][12][13][14][15][16]. In mice, the knockout of both copies of the PSP-encoding gene is apparently lethal [17], further confirming the crucial biological role of this enzyme and of the phosphorylated pathway.…”
Section: Introductionmentioning
confidence: 99%